Pengaruh Kualitas Layanan terhadap Kepuasan Jamaah Umroh di Hajar Aswad Mubaroq - Saimona, Nur; Ulfah, Yetty Faridatul; Nugroho, Nurman Ando Setianas; Alhasbi, Faruq; Faraba, Karina Sofiananda Armaza (Pawarta: Journal of Communication and Da'wah, 2024)
Indonesia with a large Muslim population is a potential market for the Umrah travel business. Hajar Aswad Mubaroq is one of the companies that strives for the desires of the Muslim community in Solo Raya for the Umrah pilgrimage. Consumer satisfaction is an absolute that can be achieved by providing good service quality. That way, the company can excel and become a trusted partner in organizing Umrah. This study aims to see how service quality affects pilgrim satisfaction. This study was conducted using a survey and analyzed descriptively quantitatively. The participating samples were 80 respondents, who were Hajar Aswad Umrah pilgrims from March to August 2023. The results showed that service quality influence on pilgrim satisfaction. Value of tstatistics was greater than ttable with the value of the relationship between service quality and satisfaction proven significant. In addition, it was found that 17.4% of pilgrim satisfaction was influenced by service quality. Based on these results, the author suggests that it is important to make pilgrims satisfied by providing quality services. There are many antecedent factors that will benefit the company through satisfaction, so more efforts are needed in providing quality service to Umrah pilgrims.